(10+x)10=(11+9)9

Simple and best practice solution for (10+x)10=(11+9)9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10+x)10=(11+9)9 equation:


Simplifying
(10 + x) * 10 = (11 + 9) * 9

Reorder the terms for easier multiplication:
10(10 + x) = (11 + 9) * 9
(10 * 10 + x * 10) = (11 + 9) * 9
(100 + 10x) = (11 + 9) * 9

Combine like terms: 11 + 9 = 20
100 + 10x = (20) * 9

Multiply 20 * 9
100 + 10x = 180

Solving
100 + 10x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-100' to each side of the equation.
100 + -100 + 10x = 180 + -100

Combine like terms: 100 + -100 = 0
0 + 10x = 180 + -100
10x = 180 + -100

Combine like terms: 180 + -100 = 80
10x = 80

Divide each side by '10'.
x = 8

Simplifying
x = 8

See similar equations:

| n^2+n-512=0 | | 3x+6+6x=69 | | x+(x+7)+x+(x-7)= | | 14k+-8+9=-13 | | (2x+2)30=(2x+4)27 | | 9x+4-2x=3(x+8) | | 2-3x=38 | | 3y*9y^2= | | (10+3+2x)10=(9+3x)9 | | 11x-104=2x-5 | | 4x-3+5x=25 | | 20*8x+0.2*1000=40*8x | | 0=x^2+8x+14 | | (3x-35)+(5x-25)=180 | | 124=6x+d | | 2(x-4)=x+-12+2x | | 124=6x+4 | | 0=-16t^2+380 | | -2y+1=17 | | xy*3x= | | (X+3)6=(x+1)7 | | 8p*2p-7=32 | | y=-16t^2+380 | | 33x+x^2-370=0 | | 13-3x=4(y-2) | | (9+x)9=15(15) | | r*(7+10)=24 | | 5y-2-[6-(3-y)]=4(y-3)+7 | | 18x=9(20) | | (8+2+x)8=(9+x-1)9 | | 5p*3=10 | | 9+7x+x=38 |

Equations solver categories